For a genealogical and epistemological reconstruction of the concept of metacognition - González de Requena Farré, Juan Antonio (Revista de Psicología, 2010)
In the last decades, there has been an increasing investigation on metacognition, which has made familiar to us meta-terms like metaknowledge or metalearning, among others. In this article, we try to reconstruct the previous models on metacognition and recent metacognitive paradigms. We also inquire epistemological implications and rethorical and socio-historical conditions of the coining and circulation of this metacognitive lexicon.